Demokrasi dan Syura: Persepektif Islam dan Barat - Muhammad Ichsan (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
In this globalization era, the term of democracy has been part of political  culture in Muslim society, which unintentionally hindered the term of syura as  Muslim political reference. In fact, that democracy and syura are two different  concepts in Islamic discourses. The concept of democracy, which is understood,  developed and introduced by West to Muslim, is not very applicable in Muslim  world. It is because the whole concept of western democracy unlikely relevant with  Quran and Prophet Tradition. Western democracy, for instance, positions people as  the owner of the highest sovereignty. It means that whatever the people’s words, they  will be treated as a truth, although they might be wrong. While syura, as Muslim  political reference, perceives Allah as the owner of the highest sovereignty.  Humankind is commanded to apply the concept. If Muslims are going to apply any political will, they must firstly consult to the Quran and Sunnah whether the will is  applicable or not.Abstrak: Kata demokrasi di era globalisasi dewasa ini sudah membudaya dan  dipraktekkan dalam kehidupan masyarakat muslim, sehingga kata syura yang  merupakan acuan umat Islam dalam menjalankan kehidupan dalam masyarakat  hampir dilupakan. Padahal antara demokrasi dan syura terdapat perbedaan dalam  kajian Islam. Demokrasi yang dipahami dan dikembangkan oleh dunia barat kepada  dunia Islam tidak semuanya dapat diterima dan diterapkan di dunia Islam, karena  banyak hal yang terkadang tidak sesuai dengan ketentuan-ketentuan yang telah  digariskan dalam al-Qur’an dan Sunnah Rasulullah Saw. Misalnya kalau demokrasi  yang dipahami barat kedaulatan tertinggi berada di tangan rakyat, apa yang dikatakan  oleh rakyat itulah yang benar walaupun terkadang hal tersebut tidak benar. Sedangkan  dalam Islam, kedaulatan tertinggi berada di tangan Allah Swt, manusia hanya  diberikan amanah untuk melaksanakannya saja. Bila ada hal-hal yang ingin  dilakukan, maka harus dikembalikan kepada al-Qur’an dan Sunnah untuk mengetahui  ketentuan apakah boleh dilaksanakan ataupun tidak.